Elevated TyG Index Predicts Incidence of Contrast-Induced Nephropathy: A Retrospective Cohort Study in NSTE-ACS Patients Implanted With DESs - Li, Mingkang; Li, Linqing; Qin, Yuhan; Luo, Erfei; Wang, Dong; Qiao, Yong; Tang, Chengchun; Yan, Gaoliang (Frontiers in Endocrinology, 2022)
Background: The triglyceride-glucose (TyG) index is a reliable and straightforward biomarker of insulin resistance and may be related to renal dysfunction. We sought to investigate the relationship between the TyG index and the incidence of contrast-induced nephropathy (CIN) in non-ST elevation acute coronary syndrome (NSTE-ACS) patients implanted with drug-eluting stents (DESs). Methods: A total of 1108 participants were recruited and divided into two groups based on the occurrence of CIN. The TyG index was calculated as ln [ fasting triglycerides (mg/dL) × fasting blood glucose (mg/dL)/2]. The baseline characteristics and the incidence of CIN between the two groups were compared, and logistic regression analysis was performed to evaluate the relationship between the TyG index and CIN. Results: 167 participants (15.1%) developed CIN. Compared with the non-CIN group, the CIN group had a significantly higher TyG index (8.9±0.7 vs. 9.3±0.7, P<0.001). After adjusting for confounding factors, the TyG index was significantly related to the increased risk of CIN irrespective of diabetes mellitus, behaving as a J-shaped non-linear association. In addition, further subgroup analysis showed that there was a significant gender difference in the relationship between the TyG index and CIN. Moreover, the receiver operating characteristic (ROC) curve analysis indicated that the risk assessment performance of the TyG index was superior to other single metabolic indexes. Adding the TyG index to the baseline model showed an increase in the area under the curve from 0.713(0.672-0.754) to 0.742(0.702-0.782) and a continuous net reclassification improvement of 0.120(0.092-0.149). Conclusion: A high TyG index is significantly and independently related to the incidence of CIN in NSTE-ACS patients firstly implanted with DESs. Routine preoperative assessment of TyG index could help reduce CIN by highlighting a potential target for intervention in the prevention.